DIFFERENT PERCENTAGE OF WATER EXCHANGE ON GROWTH OF CORAL TROUT GROUPER FINGERLING (Plectropomus leopardus) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2010)
Coral trout grouper (Plectropomus leopardus) is the prospective aquaculture commodities with a high demand. Fingerling culture is the one of shortly rearing time methods for grow out in net-cages in order to produce continuously. Two hundred fishes with initial total length 16.6±0.5 cm and 72.2±7.6 g of body weight were stocked in each of three of concrete tanks of 4m3 seawater. Water replace as a treatment was applied i.e. A (200%/day), B (300%/day) and C (400%/day).respectively. Feeding frequency of pellet was done twice a day of about 3 - 5% of body weight. Survival and growth of fishes were monitored during two-month period. The result showed that the different percentage of water replace had a significant role in increasing the growth and survival rate of the fishes. Water replaced of 400% daily (treatment C) gave the best survival rate (97%) and growth performance (TL 21.61±0,54 cm; BW 156.84±1.05 g). In contrast, the treatment B (300%/day) and A (200%/day) resulted in a lower survival and growth , i.e. (SR 95.5%; TL 19.51±0.52 cm; BW 140.96±0.08 g) and A (SR 93%; TL 19.08±0.30 cm; BW 132.2±2.65 g)., respectively.Keywords: Coral trout grouper, growth, survival rate, water exchange